Depression can also be childhood depression (Journal of Parents and Teachers, 2014)
Depression ranks high on the list of mental problems, with 15-20% of the population suffering from depression. Research has found that it may be due to psychosocial factors, such as changes in the environment or ways of coping with stress; genetic factors or biological factors (hormonal imbalance or imbalance in neurotransmitter levels, etc.).However, depression can also be suffered by children and if left untreated can lead to subsequent problems in adolescence and adulthood. The article identifies and explains with facts ten myths about childhood depression.
Keywords: childhood depression; mental problems; myths